GERAKAN TRASNASIONAL DAN PARTISIPASI PENGEMBANGAN PENDIDIKAN (studi kasus pada pesantren salafi jihadi di NTB) - Abdul Malik (Edu Sociata : Jurnal Pendidikan Sosiologi, 2023)
After the reformation era in 1998, the variants of the pesantren experienced significant development, among the pesantren that experienced development were the salafi pesantren. Along with changes in community conditions and the national political situation, Salaf Islamic boarding schools with salafi patterns developed into three new types. This study aims to reveal national insight in the Salafi Jihadist Islamic boarding school, which has been suspected of being affiliated with radical Islamic movement groups. The method used in this research is applied qualitative research with an Interpretive Phenomenology (IP) approach. The data were critically analyzed based on the results of in-depth interviews. The survey sample respondents were selected purposively, which were in-depth interview sources from pesantren stakeholders. This research was conducted in 8 provinces: Aceh, Banten, West Java, Central Java, East Java, South Kalimantan, South Sulawesi, and West Nusa Tenggara. The findings of this study indicate that salaf pesantren with a jihadist salafi pattern are more susceptible to being infiltrated by "radical" Islamic movement groups with an indication that the pesantren model does not have a strong relationship with the government, tends to view the government as a thogut and views that activities respect the red and white flag of the law is illegal